Being with Busyness : zen ways to transform overwhelm and burnout - Pháp Huu Brother, ....-; Confino, Jo, ....- (Berkeley : Parallax Press, 2024)
Simple mindfulness practices to reconnect you with your deepest aspirations. In this fast-paced, complex world, how do we uphold our ideals without burning out? Being with Busyness explores the modern diseases of overwhelm and burnout, and how the power of deep rest, mindfulness, and compassion can help us when we run out of energy and inspiration. Process suffering, Regain balance, Set healty boundaries, Rest and nourish ourselves, Bring back happiness and joy into our lives. With examples drawn from real life on the spiritual road, authors Brother Phap Huu and Jo Confino share candid stories, timeless wisdom, and the simple yet effective practices they follow dialy for a dynamic and balanced way of life.
Keywords: Burn-out